Fundamental Components of Undergraduate Exit Exams: A Systematic Literature Review of the Development, Administration, Feedback, and Remediation - Samson Worku Teshome (ANWARUL, 2025)
Exit examinations in higher education serve as critical assessments to evaluate students’ readiness for professional practice upon graduation. This study systematically reviews how exit exams are designed, administered, and followed up with feedback and remediation, aiming to identify best practices and areas needing improvement. Using the PRISMA methodology, a comprehensive literature search was conducted across databases including PubMed, JSTOR, and Google Scholar. Out of numerous articles screened, 22 studies were selected, covering disciplines such as medicine, pharmacy, aviation, and engineering. The analysis revealed that exit exams are most effective when aligned with curricular content and developed in collaboration with field experts. Key themes emerged around equitable exam administration, emphasizing accessibility for students with disabilities and diverse backgrounds. Post-exam processes such as timely and constructive feedback were found to be essential for student growth, while remediation efforts were most beneficial when focused on learning support rather than mere exam repetition. Despite these strengths, recurring challenges include inequitable exam design, insufficient institutional support, and limited access to preparation resources. To address these issues, the study recommends enhanced collaboration between institutions, students, and industry stakeholders; adoption of adaptable exam formats; and the development of robust support systems. Ultimately, exit exams should function not only as summative assessments but as formative tools guiding students toward lifelong learning and professional competence.